2023
DOI: 10.1021/acs.langmuir.2c02763
|View full text |Cite
|
Sign up to set email alerts
|

Contact Angle Measurement on Curved Wetting Surfaces in Multiphase Lattice Boltzmann Method

Abstract: Contact angle is an essential physical quantity that characterizes the wettability of a substrate. Although it is widely used in the studies of surface wetting, capillary phenomena, and moving contact lines, the contact angle measurements in simulations and experiments are still complicated and time-consuming. In this paper, we present an efficient scheme for the measurement of contact angle on curved wetting surfaces in lattice Boltzmann simulations. The measuring results are in excellent agreement with the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…20,21 Prior experimental and theoretical works have shown that chemical patterning can also induce stick-slip motion of droplets on inclined substrates. [22][23][24][25] All the works mentioned above that investigate substrates with topography involve multiple topographical defects. But it is also important to consider the case of a single defect on a substrate to gain fundamental understanding of how the different geometric features of a defect influence droplet motion.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 Prior experimental and theoretical works have shown that chemical patterning can also induce stick-slip motion of droplets on inclined substrates. [22][23][24][25] All the works mentioned above that investigate substrates with topography involve multiple topographical defects. But it is also important to consider the case of a single defect on a substrate to gain fundamental understanding of how the different geometric features of a defect influence droplet motion.…”
Section: Introductionmentioning
confidence: 99%
“…These patterns not only provide visual information about the behavior of droplet impacts but also lay the foundation for further in-depth study and theoretical analysis. By adjusting various parameters, such as geometrical parameters, , fiber surface wettability, impact conditions, , fiber inclination, and fiber shape, researchers have been able to record a series of typical images depicting droplet impact on a single fiber. In this regard, Hung et al .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, when a droplet impacts a hydrophilic fiber, three flow patterns can occur: double membrane fall, single membrane fall, and single droplet fall. Conversely, when a droplet impacts a superhydrophobic fiber, only the double membrane fall phenomenon is observed. Moreover, in the case of droplets impacting superhydrophobic fibers, researchers have also observed the formation of unstable “wing-shaped” liquid columns at the end of the retraction process, known as convergent fragmentation . The eccentric impact of the droplet also significantly affects its morphology.…”
Section: Introductionmentioning
confidence: 99%